Multi-directional Changes in 8-OHdG Concentration in Saliva during HER2 Expression in Breast Cancer - Dyachenko, E.I.; Pahalkova, E.V.; Sarf, E.A.; Bel`skaya, L.V. (Biomedical Chemistry: Research and Methods, 2024)
The purpose of this work was to evaluate changes in the structure of 8-OHdG in saliva in patients with breast cancer depending on molecular biological subtypes. The findings show that decreased salivary 8-OHdG concentrations in the HER2-positive group rapidly correlated with decreased cell differentiation and high Ki-67 levels, reflecting the aggressive nature of the tumor disease and poor survival prognosis. Thus, the presence of high levels of 8-OHdG in the oral cavity may lead to the development of the role of a biological marker of the HER2-positive group with a poor prognosis of breast cancer and can be used as an additional method of diagnosis, patient condition and response to therapy.